Frequency of probable social media addiction and correlates of problematic social networking sites use in a sample of transgender adults - Katharina Grupp; Marco Blessmann; Hans-Helmut König; André Hajek (Heliyon, 2025)
Aim: Transgender people face many unique challenges. Thus, some of them report excessive use of social media. Our aim was to identify the frequency of social media addiction and to investigate the factors associated with problematic social networking sites use exclusively amongst transgender adults in times of the Covid-19 pandemic. Subjects: We used data from the “Transgender Survey” HH-TPCHIVG (n = 104 in the analytical sample). Transgender people from self-help groups were involved in gathering information about gender-affirming surgery at a German hospital were included. Specific exclusion criteria did not exist. The validated Bergen Social Media Addiction Scale served as a tool to quantify probable social media addiction. Results: In sum, 20.5 % of the transgender people are probably addicted to social media. Regressions showed that problematic social networking sites use was significantly positively associated with the presence of a migration background (β = 2.41, p < 0.05), and a higher frequency of sports activities. Conclusion: In conclusion, our study stressed the challenge of probable social media addiction among transgender people. Knowledge about the correlates of problematic social networking sites use may assist in addressing individuals at risk. The associations identified in this study could be explained, by, among other things, body dissatisfaction (especially with regard to sporting activities) or increased internet contacts (for people with a migration background). Efforts to reduce social media addiction (e.g., awareness-raising, promotion of offline activities, using role models) could prove effective in this group, pending longitudinal research.